2014
DOI: 10.1016/j.ijid.2014.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of the GeneXpert C. difficile PCR assay and C. diff Quik Chek Complete kit assay for detection of Clostridium difficile antigen and toxins in symptomatic community-onset infections

Abstract: The GeneXpert assay was more sensitive than QCC for the detection of C. difficile toxin in stool, but both assays were highly specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
(33 reference statements)
2
13
0
1
Order By: Relevance
“…We also showed that PCR-positive samples were split between toxin-negative and toxinpositive EIA results. This finding is similar to findings of other studies that showed toxin EIA testing to have decreased sensitivity compared to that of PCR testing (22)(23)(24).…”
Section: Discussionsupporting
confidence: 91%
“…We also showed that PCR-positive samples were split between toxin-negative and toxinpositive EIA results. This finding is similar to findings of other studies that showed toxin EIA testing to have decreased sensitivity compared to that of PCR testing (22)(23)(24).…”
Section: Discussionsupporting
confidence: 91%
“…The samples were tested immediately upon arrival in the ARL by GDH test and for C. difficile toxin detection using GeneXpert [25]. All samples were then cultured on Cycloserine Cefoxitin Fructose Agar (CCFA) (Oxoid, Basingstoke, UK).…”
Section: Microbiological Testingmentioning
confidence: 99%
“…In contrast to our findings, previous reports suggest that C. difficile toxin EIA lacks sensitivity but shows better specificity compared to molecular test and the cell culture cytotoxin neutralization assay for detection of C. difficile toxin. [ 8 9 10 ] However, emerging data now indicate that sensitivity and specificity of the EIA assay might be related to the C. difficile ribotype present in the stool sample being tested. [ 11 ] We speculate that this might explain the differences in the sensitivity and specificity of the QCC-EIA assay observed in our study compared to other reports.…”
Section: Discussionmentioning
confidence: 99%